METHODOLOGICAL PLURALISM AND THE DEVELOPMENT OF SCIENTIFIC ARGUMENTATION IN PHYSICS TEACHING - Martins Galvao, Idmaura Calderaro [UNESP]; Castro Monteiro, Isabel Cristina de [UNESP]; Alvarenga Monteiro, Marco Aurelio [UNESP] (Univ Francisco Jose Caldas, Fac Science & Education, 2020)
We studied the use of methodological pluralism in physics classes for the improvement of secondary school students' scientific argumentation, in the heartland of Sao Paulo state. The research was carried out during a semester of work, using various teaching methodologies: experimental and demonstration activities, as well as activities using information and communication technologies and projects as problem-solving strategies. The argumentations developed were collected through interviews in focus groups and also through the presentation of projects. We analysed the arguments according to the elements of the superstructure proposed in the Toulmin pattern. The data analysis revealed evidence of an evolution in the argumentation quality of the students, who initially demonstrated few characteristic elements of the Toulmin pattern but, throughout the process, integrated aspects of a higher argumentative level. Therefore, we showed that the use of methodological pluralism in the classroom contributes to the development of scientific argumentation throughout the teaching and learning process of physics.
Keywords: Teaching and training; Language sciences; Physics teaching